Importance of plaque volume and composition for the prediction of myocardial ischaemia using sequential coronary computed tomography angiography/positron emission tomography imaging - Wang Xu; van den Hoogen Inge J.; Butcher Steele C.; Kuneman Jurrien H.; de Graaf Michiel A.; Kamperidis Vasileios; Boukes Mark; Maaniitty Teemu; Schultz Jussi; van Rosendael AR; Saraste Antti; Knuuti Juhani; et al. (OXFORD UNIV PRESS, 2025)
Aims
Coronary atherosclerosis with a large necrotic core has been postulated to reduce the vasodilatory capacity of vascular tissue. In the present analysis, we explored whether total plaque volume and necrotic core volume on coronary computed tomography angiography (CCTA) are independently associated with myocardial ischaemia on positron emission tomography (PET).
Methods and results
From a registry of symptomatic patients with suspected coronary artery disease and clinically indicated CCTA with sequential [15O]H2O PET myocardial perfusion imaging, we quantitatively measured diameter stenosis, total and compositional plaque volumes on CCTA. Primary endpoint was myocardial ischaemia on PET, defined as an absolute stress myocardial blood flow ≤2.4 mL/g/min in ≥1 segment. Multivariable prediction models for myocardial ischaemia were consecutively created using logistic regression analysis (stenosis model: diameter stenosis ≥50%; plaque volume model: +total plaque volume; plaque composition model: +necrotic core volume). A total of 493 patients (mean age 63 ± 8 years, 54% men) underwent sequential CCTA/PET imaging. In 153 (31%) patients, myocardial ischaemia was detected on PET. Diameter stenosis ≥50% (P < 0.001) and necrotic core volume (P = 0.029) were independently associated with myocardial ischaemia, while total plaque volume showed borderline significance (P = 0.052). The plaque composition model (χ2 = 169) provided incremental value for the prediction of ischaemia when compared with the stenosis model (χ2 = 138, P < 0.001) and plaque volume model (χ2 = 164, P = 0.021).
Conclusion
The volume of necrotic core on CCTA independently and incrementally predicts myocardial ischaemia on PET, beyond diameter stenosis alone.